Bagian Warisan Anak Perempuan Pada Penetapan Nomor 18/pdt.p/2021/ms.lgs Dalam Perspektif Maqashid Syariah - Zulham Wahyudani (Hukum Keluarga Islam IAIN LANGSA, 2022)
This study tells about the decision of the Syari'yah Court of Langsa City Number 18/Pdt.P/2021/MS.Lgs. Based on the results of the decision, there was an asymmetry between the results of the decision and the provisions that apply to the fiqh of Mawaris, namely: veiling brothers and daughters. This study tries to harmonize the results of the decision with the sharia maqahid theory. Both maqashid amah, distinctive, khithab and law. This research is classified as literature research with a qualitative approach. The methodology in this article uses legal research methods. The results of the study concluded; the determination of the Langsa City Syariyyah Court Number 18/Pdt.P/2021/MS.Lgs does not violate the maqashid theory. One of the purposes of not giving inheritance to biological brothers is to replace part of his inheritance as a living that he must give to his biological children. This is in accordance with the objectives of the global sharia which aims to uphold justice and create a safe and sustainable life.